UJI EFEKTIVITAS EKSTRAK ETANOL DAUN KALAKAI (Stenochlaena palustris (Burm.F) Bedd) TERHADAP PENURUNAN KADAR GLUKOSA DARAH PADA TIKUS PUTIH JANTAN YANG DIINDUKSI GLUKOSA - Fakhruddin, Fakhruddin; Billi, Joseph; Dwiannur, Febriandi Ramadhan; A'yun, Qurrotul; Hatimah, Naimi Amalia; Rahimamullah, M Arsyad (Jurnal Borneo Cendekia, 2024)
Diabetes Mellitus is characterized by elevated blood glucose levels. Kalakai leaf is one of the plants formulated as a traditional remedy to address Diabetes Mellitus. One of the compounds found in Kalakai leaf extract is flavonoids, which act as antioxidants and help reduce blood glucose levels. The aim of this study is to investigate the effect of ethanol extract of Kalakai leaf on blood glucose reduction in male white rats induced by glucose. This experimental study employed a pre-test and post-test control group design. Kalakai leaf was used as the sample, and 15 male white rats were divided into 5 groups, each consisting of 3 rats. Group 1 was given a treatment of CMC suspension, Group 2 received glibenclamide suspension, Group 3 was treated with 50 mg/kgBB of Kalakai leaf ethanol extract, Group 4 received 100 mg/kgBB of Kalakai leaf ethanol extract, and Group 5 was given 150 mg/kgBB of Kalakai leaf ethanol extract. The results of this study showed that Kalakai leaf ethanol extract had an effect on lowering blood glucose levels. However, the extract at a dose of 150 mg/kgBB was more effective in significantly reducing blood glucose levels compared to the 50 mg/kgBB and 100 mg/kgBB doses. This study concludes that Kalakai leaf ethanol extract has the potential to lower blood glucose levels in male white rats induced by glucose.